Implementasi Rehabilitasi terhadap Penyalahgunaan Narkotika : Studi Kasus: di Badan Narkotika Nasional Kota Samarinda - Rani Aulia; Orin Gusta Andini; Sulung Nugroho (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
This study aims to analyze the implementation of rehabilitation at the investigation stage for drug abuse cases and the integrated assessment mechanism in influencing decisions to continue or terminate legal proceedings against drug users in Samarinda City. Drug abuse remains a serious issue in Indonesia, with more than 60% of inmates in correctional institutions being convicted of narcotics-related crimes. This condition indicates that conventional punitive approaches have not been effective in reducing drug abuse; therefore, the application of rehabilitative legal policies, as stipulated in Law Number 35 of 2009 on Narcotics and Supreme Court Circular Letter (SEMA) Number 04 of 2010, is necessary. This research employs a socio-legal research method with a qualitative approach, conducted through in-depth interviews with investigators at the Samarinda City Police (Polresta Samarinda) and officers at the National Narcotics Agency (BNN) of Samarinda, as well as a literature review of relevant laws and legal materials. The findings reveal that the implementation of rehabilitation at the investigation stage in Samarinda City has not been fully effective, due to limited resources, lack of inter-agency coordination, and the persistence of a repressive paradigm in handling narcotics cases.